Tribological Evaluation and Model of Wear Behavior in the Boundary Lubrication of the Contact Surfaces of Cycloidal Reducers - Juozas Padgurskas; Oleksandr Dykha; Raimundas Rukuiža; Darius Volskis; Rima Mickevičienė; Giorgi Abramishvili; Jumber Iosebidze (Lubricants, 2025)
Cycloidal reducers are widely used in precision drive systems due to their reduced backlash in meshing and compact design. However, their operational durability is limited by surface wear and lubricant degradation under elevated contact loads and boundary lubrication conditions. This study introduces a modified wear prediction model based on four-ball tribological testing, specifically adapted to simulate the complex tribological conditions in cycloidal gear contacts. The model incorporates the total acid number (TAN) and thermal conductivity coefficient of the lubricant as dimensionless factors, enabling a dynamic prediction of wear intensity as the lubrication degrades. This innovation allows an accurate estimation of service life and reliability in high-load, small-contact-area mechanical systems and offers a practical diagnostic tool for the predictive maintenance of gear transmissions.